Evaluating vibrating line location with respect to palatine fovea in various soft palate types - M. Aamir Ghafoor Chaudhary, Syed Hammad Azeem Rizvi, Afsheen Zakir, Faiza Awais, Noor Fatima, Arooj Fatima, Sajid Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of the location of vibrating line in relation to palatine fovea in Class I, II and III soft palate types among patients at Islamic International Dental College, Islamabad. Study design: A cross-sectional observational study Place and duration: Prosthodontic Dept of Islamic International Dental College, Riphah International University, from 2nd October 2021 till 2nd January 2022. Methodology: A total of 200 subjects were selected and clinically examined for various locations of vibrating line with respect to palatine fovea in soft palate types (I, II, III). Phonation method ‘Ah’ was used to locate vibrating line location. Results: The vibrating line location was anterior to palatine fovea in 72.7%, 64.1%, 50% of subjects with Class I, II, III soft palate. 16.5%, 25.6%, 22.7% subjects had vibrating line locating at fovea palatine in Class I, II, III soft palate types. Least observed location was the posterior location of vibrating line; 10.8%,10.3% 27.3% in all soft palate types (class I, II, III). In-significant association with age, gender and soft palate types was seen with location of vibrating line. Conclusion: The vibrating line was located predominantly anterior to palatine fovea in all three soft palate types. Keywords: Dentures, Post dam area, Palatine Fovea, Retention, Soft Palate Contours, Vibrating line.